Dietary canthaxanthin improves egg production rate through regulating hepatic lipid metabolism and redox status in indigenous chickens - Chen, Jie; Yu, Sumeng; Zhang, Xiaofeng; Song, Yiping; Zhou, Xiaoyun; Xiao, Mei; Liu, Wenchao; An, Lilong (Frontiers in Veterinary Science, 2025)
Oxidative stress during egg production disrupts hepatic lipid metabolism and impairs laying performance in hens. This study investigated the effects of dietary canthaxanthin (CX) supplementation (0, 4, 6, 8, 10 mg/kg) on hepatic histomorphology, lipid metabolism, antioxidant capacity, and egg production in indigenous chickens reared under controlled conditions (25 ± 2°C, 65–75% humidity). A total of 180 one-day-old female chickens were randomly assigned to a control group (NC) and four treatment groups (NT1, NT2, NT3, NT4). The trial lasted 9 weeks, with sampling performed at weeks 3, 6, and 9. During the experimental period, compared with the control group, dietary CX supplementation improved the liver weight, egg production rate, serum HDL-C, TG, TC in liver and serum (p < 0.05). At week 6, dietary 6 mg/kg CX supplementation significantly reduced yolk TG and serum LDL-C levels (p < 0.05), while 10 mg/kg CX significantly increased serum T-AOC and SOD activities (p < 0.05). At week 3, 10 mg/kg CX significantly enhanced serum CAT and GSH-Px activities (p < 0.05). At week 9, 8 mg/kg CX significantly decreased serum MDA levels (p < 0.05). Histological analysis revealed that CX improved liver cell structure, reducing vacuolar degeneration and lipid droplet deposition. Additionally, CX significantly upregulated the expression of SREBP-1c, FASN, ACC, ME, and LXRα in the liver (p < 0.05). In conclusion, dietary supplementation with CX demonstrates beneficial effects on lipid metabolism, antioxidant capacity, and egg production in laying hens, with an optimal recommended dosage of 8 mg/kg. This study provides theoretical evidence supporting CX as a functional feed additive to ameliorate lipid metabolic disorders and enhance laying performance in poultry production.